Islam dan Fenomena Globalisasi: Analisis Ayat Al-Qur’an dengan Metode Tafsir Maudhui - Ahmad Satria; Andi M. Arfandi; Ara Farhanul Ibad; Muhammad Sa’id; Asep Abdul Muhyi (Gunung Djati Conference Series, 2023)
This study examines Islam and Globalisation which is one of the discussions on contemporary issues in the perspective of the Qur'an. By using the maudhu'i method of interpretation, namely by presenting the verse, verse translation, asbabun nuzul, munasabah and its interpretations. It starts by selecting word equivalents related to the word globalisation in the Qur'an, then quoted and examined with the maudhu'i interpretation method. This research presents the issue of how Islam relates to an era that we call the era of Globalisation. It is an era that encourages us to keep up with the flow with various even technology. Globalisation builds a vision of creating a modernist life, which provides convenience to humans in the continuity of human life. In this era, humans seem to have no barrier to do any activity. However, this paper will not explore all of the above issues, this paper will focus more on the issue of Islam and globalisation.